The Role of Direct Air Capture in Mitigation of Anthropogenic Greenhouse Gas Emissions - Beuttler, Christoph; Charles, Louise; Wurzbacher, Jan (Frontiers in Climate, 2019)
In recent years Direct Air Capture (DAC) has established itself as one promising approache to Atmospheric Carbon dioxide Removal (CDR) also referred to as Negative Emissions. However due to the amounts likely needed to be removed CDR Technologies (CDRTs) like DAC will only become climate relevant if they reach gigaton scale fast, around the middle of this century. The paper will give a brief insight into DAC and in particular, the modular low temperature DAC technology developed by Climeworks of Switzerland. It will discuss potential co benefits, in particular in relation to the Sustainable Development Goals (SDGs) of the United Nations and conclude by suggesting some policy approaches on how a climate relevant scale could be achieved in time.